KRIYA DAN DESAIN MENUJU PERKEMBANGAN KEKRIYAAN INDONESIA - Zainul Arifin MA (Universitas Islam Nahdlatul Ulama Jepara, 2016)
ABSTRACT Kriya in the context of the past is defined as an art product that contained the charge aesthetic value, symbolic, philosophical, and functional. The craft in the present context has a different understanding of that; can produce functional products and can produce art that is an expression of the individual for the sake of artistic prestige. Kriya have common terms and have many of the terms derivatives namely: Craft Art, Craft expression, Craft Design, Craft Design, Craft Product, and Contemporary Craft. These terms are essentially can be classified into two categories: the craft of design and craft art. The basic differences between the two categories lies in the motivation in the creation of its products. Kekriyaan activities should be conducted in order to craft an overall understanding, concerning the categorization in the craft, it became clear, that the